Attention Deficit Hyperactivity Disorder and Social Anxiety in Istanbul Heavy Metal Bar Patrons - TOPÇUOĞLU, VOLKAN (GALENOS YAYINCILIK, 2011)
Objective: We aimed to examine the heavy metal bar patrons in Istanbul by means of self-reported questionnaires for psychiatric disorder symptoms. Material and Methods: Seventy-one volunteers from 4 popular heavy metal bars were included to the study. The Beck Depression Inventory, the Liebowitz Social Anxiety Scale (LSAS), the Adult Attention Deficit Disorder/Attention Deficit and Hyperactivity Disorder (ADD/ADHD) Scale and the Michigan Alcoholism Screening Test (MAST) were administered to the participants. Results: One fourth of the participants (25.4%) were under high risk for a depressive episode (BDI > 17), 22 (32.3%) reported significant social anxiety (LSAS > 30), and 41(57.7%) showed moderate ADHD symptoms (Adult ADD/ADHD scale: 20-59). According to BDI score participants who were under the risk for depression showed higher scores in Adult ADD/ADHD scale scores than that of participants who were not under a risk for depression (p=0.001 for attention deficit; p=0.003 for hyperactivity; p=0.002 for impulsivity; p=0.001 for total score). In the study group, ADD/ADHD scale attention deficit score was positively correlated with the total fear, total avoidence and the total scores of LSAS (r=.359 p < 0.01; r=.332 p < 0.01; r=.358 p < 0.01, respectively). Conclusion: Heavy metal bar patrons appear to be a particular social group with an increased risk of psychopathology.
Keywords: Heavy metal; music preference; bar; social anxiety; ADHD; DEFICIT/HYPERACTIVITY DISORDER; MUSIC PREFERENCE; COMORBIDITY; ADULTS; ADHD; DRINKING; CHILDREN